Bankart versus Latarjet operation as a revision procedure after a failed arthroscopic Bankart repair - Elamo S; Selänne L; Lehtimäki K; Kukkonen J; Hurme S; Kauko T; Äärimaa V (United States, 2022)
Background: An arthroscopic Bankart operation is the most common operative procedure to treat shoulder instability. In case of recurrence, both Bankart and Latarjet procedures are used as revision procedures. The purpose of this study was to compare the re-recurrence rate of instability and clinical results after arthroscopic revision Bankart and open revision Latarjet procedures following failed primary arthroscopic Bankart operations.
Methods: Consecutive patients operatively treated for shoulder instability at Turku University Hospital between 2002 and 2013 were analyzed. Patients who underwent a primary arthroscopic Bankart operation followed by a recurrence of instability and underwent a subsequent arthroscopic Bankart or open Latarjet revision operation with a minimum of 1 year of follow-up were called in for a follow-up evaluation. The re-recurrence of instability, Subjective Shoulder Value, and Western Ontario Shoulder Instability index were assessed.
Results: Of 69 patients, 48 (dropout rate, 30%) were available for follow-up. Recurrent instability symptoms occurred in 13 patients (43%) after the revision Bankart procedure and none after the revision Latarjet procedure. A statistically and clinically significant difference in the Western Ontario Shoulder Instability index was found between the patients after the revision Bankart and revision Latarjet operations (68% and 88%, respectively; P = .0166).
Conclusions: The redislocation rate after an arthroscopic revision Bankart operation is high. Furthermore, patient-reported outcomes remain poor after a revision Bankart procedure compared with a revision Latarjet operation. We propose that in cases of recurring instability after a failed primary Bankart operation, an open Latarjet revision should be considered.